Efektivitas Pembelajaran Menggunakan Alat Peraga Roda Pecahan terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas IV SDN 13 Singkawang - Murniati Murniati; Erdi Guna Utama; Emi Sulistri (Departement of Mathematics Education, 2022)
This study aims to determine the effectiveness of the use of fractional wheel props on students' mathematical problem solving abilities on equivalent fraction material. This research was conducted at SDN 13 Singkawang. The type of research used is quantitative research with the Quasi Experimental Design method with the research design used in the form of Nonequivalent Control Group Design.: Singkawang. The population in this study were all fourth grade students at SDN 13 Singkawang. The research sample was taken by total sampling technique. After taking the sample, the experimental class was selected as the IVA class, namely the Experiment class using the fractional wheel props and the control class IVB with conventional learning. The results of this study conclude that: 1) There are differences in mathematical problem solving abilities between students who take part in learning using the Fractional Wheel props and students who follow conventional learning. 2) The effectiveness of the use of the Fractional Wheel props on the mathematical problem solving ability of fourth grade students at SDN 13 Singkawang was obtained at 0.99 in the high category. 3) Student learning activities using the Wheel of Fractions props in class IV SDN 13 Singkawang obtained an active percentage of 72% and classified as active